The effect of Foundation for Active Rehabilitation camps on the quality of life of individuals with spinal cord injury - Kamińska-Gwóźdź, Ewelina; Lewicki, Romuald; Opuchlik, Anna; Włoch, Anna (Journal of Education, Health and Sport, 2018)
Introduction.The consequences of spinal cord damages rank among the most serious dysfunctions of the human musculoskeletal system. In spite of the development of medicine, the effects of treatment and rehabilitation are still insufficient for patients and their families. Purpose. The aim of this study was to determine the effect of the participation of individuals with spinal cord injury in the introductory camps organized by the Foundation for Active Rehabilitation in the subjective sense of quality of life and the meaning of life and the motivation to search for the meaning of life. Material and methods. It involved a group of 100 participants of the introductory camp organized by the Foundation for Active Rehabilitation. These same 100 subjects were then followed up three months after the end of camp. Quality of Life Index Ferrans and Powers; PIL-Test ; SONG-Test. Results. As a result of camp participation of persons with spinal cord injury in the camp, significant increase was observed in the global Quality of Life Index score, health and functioning subscale and psychological/spiritual subscale. As a result of camp attendance, global PIL test score significantly increased, while global SONG test score significantly decreased. Conclusions. Participation by individuals with spinal cord injury in the introductory camps organized by the Foundation for Active Rehabilitation has a positive impact on the subjective quality of life, strengthens sense of the meaning of life and decreases the motivation to find its purpose.